2021
DOI: 10.1155/2021/2684361
|View full text |Cite
|
Sign up to set email alerts
|

Short-Chain Fatty Acids Promote Immunotherapy by Modulating Immune Regulatory Property in B Cells

Abstract: The dysfunction of regulatory B cells (Breg) may result in immune inflammation such as allergic rhinitis (AR); the underlying mechanism is not fully understood yet. Short-chain fatty acids, such as propionic acid (PA), have immune regulatory functions. This study is aimed at testing a hypothesis that modulates PA production alleviating airway allergy through maintaining Breg functions. B cells were isolated from the blood obtained from AR patients and healthy control (HC) subjects. The stabilization of IL-10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“… 35 The increased production of propionic acid by intestinal microbiota stabilizes IL-10 expression in B cells, which promotes the efficacy of SLIT in mice with allergic rhinitis. 36 In our study, the transplantation of fecal microbiota from patients with AD who responded well to AIT alleviated AD-like symptoms in mice and induced the expansion of Tregs. The gut microbiota of AD patients undergoing AIT differed from that of untreated patients in both composition and function, while the pathways for tryptophan metabolism, butanoate metabolism, and propanoate metabolism were enriched in the gut microbiota after 1 year of AIT.…”
Section: Discussionmentioning
confidence: 57%
“… 35 The increased production of propionic acid by intestinal microbiota stabilizes IL-10 expression in B cells, which promotes the efficacy of SLIT in mice with allergic rhinitis. 36 In our study, the transplantation of fecal microbiota from patients with AD who responded well to AIT alleviated AD-like symptoms in mice and induced the expansion of Tregs. The gut microbiota of AD patients undergoing AIT differed from that of untreated patients in both composition and function, while the pathways for tryptophan metabolism, butanoate metabolism, and propanoate metabolism were enriched in the gut microbiota after 1 year of AIT.…”
Section: Discussionmentioning
confidence: 57%
“…It has been found that GZMB can not only promote apoptosis but also lyse many different substrates, including proteolysis of extracellular matrix, cell adhesion proteins and basement membrane proteins [30] . However, our previous studies have shown that GZMB can be combined with TTP, compromising the role of TTP [15] . T-bet is a transcription factor encoded by the Tbx21 gene, and its expression affects the exercise of immune function [31] .…”
Section: Discussionmentioning
confidence: 95%
“…The regulation of allergen tolerance mediated by Bregs is considered an important immune tolerance mechanism of AR [26] . PA in SCFAs can effectively alleviate AR by stabilizing the expression of IL-10 in Bregs and has certain immunoregulatory functions in allergic diseases [15] . Tristetraproline (TTP), a proline-rich molecule, can bind to IL-10 mRNA to form a complex that can induce the attenuation of IL-10 mRNA in B cells, thereby negatively regulating IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Butyrate inhibits eosinophil survival and migration ( 52 ) as well as mast cell activation ( 53 ) by inducing histone acetylation. A recent study showed that SCFAs promote the maintenance of regulatory B (Breg) cell function by stabilizing IL-10 expression in Breg cells, thereby alleviating allergic inflammation ( 54 ). In addition, acetate and butyrate have a preventive or therapeutic effect on allergic diseases by enhancing the barrier function of the intestinal epithelium ( 48 ).…”
Section: Discussionmentioning
confidence: 99%